2019
DOI: 10.3390/ma12101612
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Ceramic Brick Drying in Oven by CFD

Abstract: The drying process is a step of ceramic brick production which requires the control of process variables to provide a final product with a porous uniform structure, reducing superficial and volumetric defects and production costs. Computational fluid dynamics (CFD) is an important tool in this process control, predicting the drying physical phenomenon and providing data that improve the industrial efficiency production. Furthermore, research involving CFD brick drying has neglected the effects of oven paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…All extruded specimens were marked and subjected to a smooth drying process in the laboratory electric oven (type SCN/400/DG). The drying process consisted of three distinct phases: the humidity phase, the shrinkage phase, and the drying phase, each demanding specific attention as they may create different issues on the samples [24].…”
Section: Dryingmentioning
confidence: 99%
“…All extruded specimens were marked and subjected to a smooth drying process in the laboratory electric oven (type SCN/400/DG). The drying process consisted of three distinct phases: the humidity phase, the shrinkage phase, and the drying phase, each demanding specific attention as they may create different issues on the samples [24].…”
Section: Dryingmentioning
confidence: 99%
“…All extruded specimens were marked and subjected to a smooth drying process in the laboratory electric oven (type SCN/400/DG). The drying process consisted of three distinct phases: the humidity phase, the shrinkage phase, and the drying phase, each demanding specific attention as they may create different issues on the samples [18].…”
Section: Dryingmentioning
confidence: 99%
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%